On the essence of the content of upbringing on the basis of ethnopedagogy - Zhetpisbayeva, B.A.; Shelestova, T.Yu. (KSU Publ., 2013)
The present work investigates the issues of the content of upbringing on the basis of ethnopedagogy where ethnopedagogy is being considered and substantiated. Upbringing formed on ethnopedagogical basics can be identified as ethnic upbringing which means focusing attention on ethno specific qualities materialized in the peculiarities of culture, traditions, language, mentality, ethnic consciousness and self-consciousness in the field of upbringing and training. The criterion of ethnic identity is an objective description of its willingness and ability to perform certain ethno-social role.
Этнопедагогика негізіндегі тəрбие мазмұнының мəні туралы
О сущности содержания воспитания на этнопедагогической основе
Keywords: ethnic upbringing; ethnopedagogy; multilingual education; language learning; culture-oriented principles